The Relationship Between High-Density Lipoprotein (HDL) and Glycated Hemoglobin (HbA1C) in Type 2 Diabetes Mellitus Patients: Implications for Cardiovascular Risk - Setyoadi, Setyoadi; Ismail, Dina Dewi Sartika Lestari; Kartika, Annisa Wuri; Sari, Dewi Purnama; Septian, Angel Dwi; Lallo, Adelina Stefanie; Kurniasari, Rara (Journal of Rural Community Nursing Practice, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder marked by hyperglycemia due to insulin resistance or impaired insulin secretion. Dyslipidemia, especially low High-Density Lipoprotein (HDL), contributes significantly to cardiovascular disease risk in T2DM. Glycated hemoglobin (HbA1c) serves as the standard biomarker for long-term glycemic control. Previous studies suggested an inverse relationship between HDL and HbA1c, but results remain inconsistent, and limited evidence exists from Indonesian primary care settings. Purpose: This study aimed to examine the association between HDL cholesterol and HbA1c levels in T2DM patients at a primary healthcare center in Batu City, Indonesia. Methods: An observational analytic study with a cross-sectional retrospective design was conducted. Secondary data were obtained from medical records of T2DM patients at Puskesmas Sisir, Batu City, in July 2025. A total of 79 patients fulfilling inclusion criteria were included through total sampling. Laboratory results of HDL (mg/dL) and HbA1c (%) were analyzed. Spearman’s rank correlation test was used, with significance set at p ≤ 0.05. Results: Among the 79 respondents, most were aged 45–65 years (50.6%) and female (77.2%). The mean HDL level was 45.3 ± 8.2 mg/dL, while the mean HbA1c level was 8.2 ± 1.5%. Correlation analysis indicated a weak negative association between HDL and HbA1c (r = –0.132, p = 0.246). Although higher HDL levels tended to correspond with lower HbA1c values, the relationship was not statistically significant. Conclusions: These findings underscore the critical role of community nurses in integrating routine HbA1c and lipid profile monitoring into T2DM follow-up visits, promoting holistic cardiovascular risk assessment even when individual biomarkers show weak associations.